2006
DOI: 10.1161/circulationaha.106.657270
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Impact of the Injection of Material Into the Myocardium

Abstract: Background-To treat cardiac injuries created by myocardial infarcts, current approaches seek to add cells and/or synthetic extracellular matrices to the damaged ventricle to restore function. Because definitive myocardial regeneration remains undemonstrated, we propose that cardiac changes observed from implanted materials may result from altered mechanisms of the ventricle. Methods and Results-We exploited a validated finite element model of an ovine left ventricle with an anteroapical infarct to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
250
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(264 citation statements)
references
References 28 publications
(33 reference statements)
12
250
1
1
Order By: Relevance
“…More specifically, they demonstrated that injections of 4.5% of the LV wall volume and 20% of the stiffness of the natural myocardium into the BZ were able to decrease the fiber stress by 20% compared to control simulations with no injections. Other approaches have validated the importance of infarct compliance using FE, as well as lumpparameter models; results reveal similar overall beneficial outcomes [35,65,66]. FE models have also been employed to evaluate the effects of material volume and distribution in the myocardium and showed that they influence the extent of remodeling, depending on their pattern of injection (Fig.…”
Section: Materials Optimization: Theoretical Evaluationmentioning
confidence: 93%
See 4 more Smart Citations
“…More specifically, they demonstrated that injections of 4.5% of the LV wall volume and 20% of the stiffness of the natural myocardium into the BZ were able to decrease the fiber stress by 20% compared to control simulations with no injections. Other approaches have validated the importance of infarct compliance using FE, as well as lumpparameter models; results reveal similar overall beneficial outcomes [35,65,66]. FE models have also been employed to evaluate the effects of material volume and distribution in the myocardium and showed that they influence the extent of remodeling, depending on their pattern of injection (Fig.…”
Section: Materials Optimization: Theoretical Evaluationmentioning
confidence: 93%
“…Over the past decade, it has become clear that the mechanical changes that occur after MI must be considered when developing post-MI therapies [35,41,42]. MI leads to extracellular matrix (ECM) breakdown and results in geometric changes in both the infarcted and healthy myocardium.…”
Section: Injectable Hydrogels As Bulking Agentsmentioning
confidence: 99%
See 3 more Smart Citations